Innovations Shaping Smart Mobility. Tri-City Case Study - Adam Przybyłowski; Jagoda Rahn (Barometr Regionalny)
The 2020s are predicted to be a decade of transformation for urban mobility. Innovations in the transport sector continue to introduce new opportunities to enhance travel experiences in the cities. This is facilitated by business models that offer a range of new mobility services that provide flexible options to meet travel needs. Good mobility for citizens and businesses greatly increases the attractiveness and competitiveness of cities. The purpose of this paper is to explore the innovations shaping smart mobility in modern agglomerations taking as a case study Tri-City (Gdańsk-Gdynia-Sopot). A survey in the form of a questionnaire was created to study how smart mobility looks in the eyes of the local community. The study was conducted among a randomly selected group of respondents. The results provide some interesting conclusions. The Tri-City community is not fully aware of the fact that there are a lot of smart mobility solutions available within the area. The paper is based on the available literature sources and statistical data, as well as on the survey research study.